Using allegory to think about youth work in rich countries that fail some young people. (16th March 2019) - Emslie, Michael
ABSTRACT: This article explores the opportunities afforded by Ursula Le Guin's allegory 'The Ones Who Walk Away from Omelas' for thinking about the role of youth work in modern cities and societies that are deemed to be successful but at the same time fail some young people. Using Melbourne and Australia as examples and following Le Guin the case is made that the prosperity of 'liveable' cities and 'lucky' countries coincides with the neglect and mistreatment of some young people. The same cultural, economic and political practices and processes that produce the beauty and abundance also produce the inequalities and hardships, and these include policies inspired by neoliberalism, processes of individualisation, and utilitarianism. Unlike the ones who walk away from Omelas youth workers can stay and fight adversity and injustice, however alleviating problems young people experience is more complex than it is often thought to be. One reason this is the case is because youth work is entangled with the same range of ethical, emotional, intellectual, political, and economic circumstances that generate thriving places and disadvantaged young lives, and inadvertently youth workers can reproduce the challenging and limiting conditions faced by some young people.